Ruptured Emphysematous Prostatic Abscess Caused by K1-ST23 Hypervirulent Klebsiella pneumoniae Presenting as Brain Abscesses: A Case Report and Literature Review - Konagaya, Kensuke; Yamamoto, Hiroyuki; Suda, Tomoyuki; Tsuda, Yusuke; Isogai, Jun; Murayama, Hiroyuki; Arakawa, Yoshichika; Ogino, Hidemitsu (Frontiers in Medicine, 2022)
Emphysematous prostatic abscess (EPA) is an extremely rare but potentially fatal urinary tract infection (UTI). Here, we describe a case (a 69-year-old male with prediabetes) of ruptured EPA caused by a hypervirulent Klebsiella pneumoniae (hvKp) K1-ST23 strain, presenting as motor aphasia. Our patient presented with ruptured EPA concurrent with various severe systemic pyogenic complications (e.g., urethro-prostatic fistula, ascending UTIs, epididymal and scrotal abscesses, and liver, lung, and brain abscesses). Whole-body computed tomography (CT) and next-generation sequencing (NGS) were useful for the detection of ruptured EPA and its systemic complications, and for identification of K1-ST23 hvKp strains, respectively. Subsequently, the infections were successfully treated with aggressive antimicrobial therapy and multiple surgical procedures. This case highlights the significance of awareness of this rare entity, the clinical importance of CT for the early diagnosis of EPA, and the detection of its systemic complications, in view of hvKp being an important causative organism of severe community-acquired UTI, and the usefulness of NGS to identify hvKp strains.